Kebijakan Pengelolaan Alokasi Dana Desa dalam Meningkatkan Pemberdayaan Masyarakat di Desa Ayuhulalo Kecamatan Tilamuta Kabupaten Boalemo - Fibriyanti Lakoro; Sukrianto (Al-Muhasabah: Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This research aims to describe village fund allocation management policies in increasing community empowerment in Ayuhulalo Village, Tilamuta District, Boalemo Regency. This research method uses descriptive research with a qualitative approach. Data sources that can be used are primary and secondary data. Data collection techniques can use observation, interviews and documentation. The data analysis technique uses analysis from Milles and Huberman, by carrying out data reduction, presenting data and drawing conclusions. The results of the research show that policies in managing village fund allocation can be seen from the use of the budget in village apparatus expenditure and can be implemented well. The use of the budget is mainly for empowerment spending or spending in the development process which can be implemented very well.